Becoming a supple leopard : the ultimate guide to resolving pain, preventing injury, and optimizing athletic performance - Starrett, Kelly (Victory Belt Publishing Inc., 2015)
Based on the premise that dysfunctional movement patterns impede athletic performance, the author presents the construction and function of his own movement and mobility system, based on his midline stabilization and organization, one-joint rule and laws of torque movement principles, all to remedy body stiffness, prevent injuries and improve and extend athletic capabilities.